3D-QSAR, molecular docking, and dynamics simulation of quinazoline–phosphoramidate mustard conjugates as EGFR inhibitor - Ruslin Ruslin, Resky Amelia, Yamin Yamin, Sandra Megantara, Chun Wu, Muhammad Arba (Journal of Applied Pharmaceutical Science, 2019)
To develop novel and more potent quinazoline–phosphoramidate mustard conjugates as epidermal growth factor receptor (EGFR) inhibitor, three-dimensional quantitative structure-activity relationship [comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA)] combined with molecular docking were performed. A series of 13 compounds in the training set gave q2 values of 0.577 and 0.537, as well as r2 values of 0.926 and 0.921 for CoMFA and CoMSIA models, respectively. The contour maps that were produced by the CoMFA and CoMSIA models revealed that steric, electrostatic, and hydrophobic fields were crucial in the inhibitory activity of quinazoline–phosphoramidate derivatives. Based on the CoMFA and CoMSIA models, several novel EGFR inhibitors were designed, which established crucial interactions at the ligand binding domain of EGFR. Nearly, 100 ns MD simulation indicated the stability of the designed compounds at 100 ns, while molecular mechanics-Poisson Boltzmann surface area calculation showed that the designed compound had a higher affinity than that of the parent compound.
Keywords: 3D-QSAR, CoMFA, CoMSIA, docking, quinazoline– phosphoramidate.